Characterization of Potential Wind Generation EolioelÃtrica For Purposes: A Case Study For MaracanaÃ (CE), ParnaÃba (PI) and Petrolina (PE) - Tatiane Carolyne Carneiro (2014)
In recent years wind energy is becoming increasingly competitive on the world stage, making their participation in the electricity generation matrix presents a strong growth expectation. This dissertation initially presents an analysis of the behavior of wind at three locations in Northeast Brazil (Maracanau-CE, Petrolina-PE e Parnaiba-PI). In a second step, statistical analyzes are researched to the most appropriate behavior patterns of the observed wind resource in the three localities. In conclusion, the impact of the statistical analyzes used in the production of electricity from wind turbines is identified. In this study,historicaldata of speed and direction of wind collectedare used, during periods of: February 2012 to January 2013, to Maracanau; August 2012 to July 2013, for Parnaiba; and May 2012 to March 2013, for Petrolina. The Weibull distribution is applied to approximate the histograms of wind speed using different horizons of applications (annual, semiannual) and four different numerical methods (Empirical, Momentum, Energy Pattern Factor and Equivalent Energy) for estimation of the form and scale parameters. In addition to evaluating the application of Weibull, other frequency distributions (Normal, Gamma and Log-Normal)are analyzed, in order to obtain the best possible fit. In a last step, with the aid of RETScreen program,annual production of electricity, delivered to the grid from wind turbines,is calculated. The optimum wind speed occurred in Parnaiba (10 and 11 m / s), followed by Petrolina (8 and 9 m / s). Among all different numerical methods that was evaluated, the Equivalent Energy method presented the best performance, unlike the Energy Pattern Factor method, that presented the worst. The Weibull distribution showed good potential for setting wind data in Maracanau and Parnaiba, both located along the coastline. However, based on the wind data recorded, in Petrolina, which is located further inland, the performance was inferior. Among all the different frequency distributions that were verified, only normal distribution had an fit as good as Weibull distribution. Based on the annual electricity production estimation, Parnaiba is the city that has the best potential for energy production.